2014
DOI: 10.1242/jeb.099135
|View full text |Cite
|
Sign up to set email alerts
|

Responses ofDrosophilagiant descending neurons to visual and mechanical stimuli

Abstract: In Drosophila, the paired giant descending neurons (GDNs), also known as giant fibers, and the paired giant antennal mechanosensory descending neurons (GAMDNs), are supplied by visual and mechanosensory inputs. Both neurons have the largest cell bodies in the brain and both supply slender axons to the neck connective. The GDN axon thereafter widens to become the largest axon in the thoracic ganglia, supplying information to leg extensor and wing depressor muscles. The GAMDN axon remains slender, interacting wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…In larger flies Calliphora erythrocephala , the GF will spike only if visual and mechanical stimuli coincide (Milde and Strausfeld, ). Mu et al () recently analyzed the response of the GF in D. melanogaster to such multimodal stimuli. In their experiments, either an air puff to the fruit fly's antennae or a light‐off stimulus elicited an excitatory postsynaptic potential in the GF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In larger flies Calliphora erythrocephala , the GF will spike only if visual and mechanical stimuli coincide (Milde and Strausfeld, ). Mu et al () recently analyzed the response of the GF in D. melanogaster to such multimodal stimuli. In their experiments, either an air puff to the fruit fly's antennae or a light‐off stimulus elicited an excitatory postsynaptic potential in the GF.…”
Section: Discussionmentioning
confidence: 99%
“…They further found that intensity of responses to combined stimuli was significantly larger than the response to either the light‐off or air‐puff stimulus alone. The simultaneous paring of these two types of sensory signals seems more likely to induce reliable GF activity than when either stimulus is presented alone (Mu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We did not include ascending neurons and neck 829 motor neurons in this analysis. For the physical definitions and nomenclature of the brain neuropils, we 830 followed the virtual fly brain (http://www.virtualflybrain.org/; Ito et al 2014). Abbreviations used in the 831 document are summarized in Supplementary Table 6.…”
Section: Terminology and Neuropil Annotation 827mentioning
confidence: 99%
“…In Drosophila, relays from the glomeruli in the lateral protocerebrum projects to higher centres of processing such as the central complex (Liu et al, 2006, Strausfeld andOkamura, 2007) through the dorsal protocerebral lobes. But they also convey information to the rest of the body through interactions with the giant descending neurons (Mu et al, 2014), which project to the thoracic ganglia. Although we still do not know the function of the glomeruli and why they are gathered in a large glomerular complex in the stomatopod protocerebrum, it is likely that the large variety of shapes and sizes of glomeruli indicate different types of information inputs, possibly from different types of visual modalities.…”
Section: Glomeruli and The Glomerular Complexmentioning
confidence: 99%